THE IMPACT OF TAXES ON PRODUCTION ON INCOME DISTRIBUTION IN INDONESIA - Dasa Nugraha, Kunta Wibawa (Jurnal Kajian Ekonomi dan Keuangan, 2013)
The Indonesian economy has grown significantly since 2000, but income inequality has increased since 2001. One of the possible government tools to improve income inequality is through taxation. This paper evaluates taxes on production and their impact on income distribution using Scutella methods. The impact of taxes on production on household income distribution provides the measure for determining the tax burden for each household income groups. This method uses the National Socioeconomic Survey and the Input-Output Table for major data sources. The key finding is that taxes on production worsen income distribution and the form of this tax is regressive, especially for lower and middle income households. The other key finding is that the consumers of cigarettes have the highest burden of taxes on production. The results suggest that Indonesian taxes on production worsen income inequality and the higher effective tax rates do not mean the higher the burden of taxes on production for consumers.